Significance of SPM Additional Mathematics and Physics toward Engineering Diploma Student’s Performance at PPD Space - Usman, Sahnius; Harun, Norhaslinda; Aini Bani, Nurul; Mad Kaidi, Hazilah; Armiza Mohd Aris, Siti; Zura A. Jalil, Siti; Nabil Muhtazaruddin, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Additional Mathematics and Physics are among SPM subjects that have great influence on engineering. The continuity of these two subjects can be seen in the courses offered each semester in the Engineering Diploma Program at PPD, SPACE. Students’ ability to master the knowledge of additional mathematics and physics greatly helps in decision-making while continuing their study at PPD, SPACE. This is in agreement with the aim of the Engineering Department to produce students with a cumulative grade point average (CGPA) of over 3.00 to enable them to continue with bachelor studies as well as compete in the job market. The results suggest that students’ performance in engineering programs depends on the SPM results they have obtained. It is possible that students who scored A and B have higher CGPAs compared to those with C for Additional Mathematics and Physics. Between these two SPM subjects, a study will be conducted to see which subject has a higher impact on students’ performance.